Pengaruh Paparan Konten Media Sosial terhadap Opini Publik Generasi Z dalam Komunikasi Politik Digital - Felicia Ioandes; Riris Loisa (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
Social media platforms, particularly TikTok, have increasingly emerged as influential spaces for political communication, especially among younger generations. This study investigates the effect of exposure to TikTok content associated with the hashtag #kaburajadulu on the formation of public opinion among Generation Z users. The research is grounded in Computer-Mediated Communication (CMC) theory to examine how interaction and meaning-making processes occur within digitally mediated environments. Using a quantitative research design, the study employed a survey method involving 111 Generation Z respondents aged 13–28 who actively use TikTok. Data were analyzed through validity, reliability, and normality testing, followed by Pearson correlation and simple linear regression analysis. The findings demonstrate that the research instruments are both valid and reliable, while the data meet the assumption of normal distribution. Correlation analysis indicates a strong and statistically significant relationship between exposure to TikTok content and public opinion formation (r = 0.719). Furthermore, regression analysis reveals that TikTok content exposure has a significant positive effect on public opinion, accounting for 51.7% of the variance. These findings suggest that TikTok functions not merely as an entertainment platform, but also as a powerful arena for digital political communication capable of shaping public opinion among Generation Z. The study contributes to contemporary discussions on social media influence by highlighting the growing role of algorithm-driven content exposure in the construction of political perceptions and attitudes among young audiences. Media sosial, khususnya TikTok, semakin berperan sebagai medium komunikasi politik yang memengaruhi pembentukan opini publik di kalangan generasi muda. Penelitian ini bertujuan untuk mengkaji pengaruh paparan konten TikTok dengan tagar #kaburajadulu terhadap opini publik Generasi Z. Penelitian ini menggunakan teori Computer Mediated Communication (CMC) untuk memahami proses interaksi dan konstruksi makna dalam komunikasi berbasis media digital. Metode yang digunakan adalah pendekatan kuantitatif melalui survei terhadap 111 responden Generasi Z berusia 13–28 tahun yang aktif menggunakan TikTok. Data dianalisis menggunakan uji validitas, reliabilitas, normalitas, korelasi Pearson, dan regresi linier sederhana. Hasil analisis menunjukkan bahwa instrumen penelitian valid dan reliabel serta data berdistribusi normal. Uji korelasi menunjukkan hubungan yang kuat dan signifikan antara paparan konten TikTok dan opini publik (r = 0,719). Hasil regresi menunjukkan pengaruh positif yang signifikan dengan nilai koefisien determinasi sebesar 51,7%. Temuan ini menegaskan bahwa konten TikTok memiliki peran penting dalam membentuk opini publik Generasi Z dalam konteks komunikasi politik digital.